A Note on Lightlike Hypersurfaces of Semi-riemannian Space Form - Wang, Yaning; Liu, Ximin (Sarajevo Journal of Mathematics, 2024)
In this paper, we mainly study lightlike hypersurfaces of semi-Riemannian space form. Our main result is a classification theorem of screen conformal lightlike hypersurfaces. Also, we obtain some geometric properties of lightlike hypersurfaces with a conformal Killing distribution. 2010 Mathematics Subject Classification. 53C25, 53C50.